BLEUtalk secured voice over bluetooth - Domingo, Kyle E.; Bautista, Waldemar A. (2006)
The Bluetooth specification describes a robust, powerful and secured communication using low-cost, low-powered, and oftentimes lightweight devices. Bluetooth is not a new technology, yet its real power has not been fully harnessed until now. Today, it is not uncommon to see Bluetooth modules embedded in cellular phones, yet, mobile phone consumers but their units not because of Bluetooth but because of the camera. Bleutalk demonstrates the feasibility of Secured Multipoint audio communication using bluetooth networks combined with wired networks. It tries to deal with problems common to networks such as delay and congestion. It provides a solution to some social problems of the Filipino poor, and opens new oppotunities to business people by integrating free technologies such as Bluetooth and Java with cheap computers to build a marketable machine.
Thesis (B.S. Computer Science)--University of the Philippines, Diliman.
Keywords: Bluetooth technology; Mobile communication systems -- Security measures; BLEUtalk